Atrial Fibrillation in Hypertrophic Cardiomyopathy: Evidence-based Review About Mechanism, Complications and Management. Issue 2 (June 2020) - Arunachalam, Karuppiah; Maan, Abhishek; Chu, Antony
Abstract : Hypertrophic cardiomyopathy (HCM) is 1 of the most frequent genetic cardiovascular diseases affecting 1 out of every 500 individuals in general population. Atrial Fibrillation incidences were 3.8% per 100 patients per year and overall prevalence among HCM patients are 27.09%. Higher risk of death noted in HCM patients with atrial fibrillation. Stroke and other thrombo embolic risks are increased in such patients. Medical management using mainly betablockers or amiodarone produced variable results and high rate of recurrence. Catheter ablation reduced symptom burden and complications despite moderate recurrence. Patients with multiple repeated procedures found to have better success rate and outcomes. The complications are not high leading to increased feasibility of the procedure. More research using latest techniques in catheter ablation need to be studied.